(untitled) (Pravaha, 2020)
The investors’ prioritization towards the gold investment and capital market investment is really interesting issue. To clear the issue in the context of Nepal,the research paper seeks the relationship between gold prices on Nepalese capital market. The descriptive and analytical research design has been adopted in the study. The study is based on quantitative approach. The data has been collected from July 2015 to July 2018. The information on market index and gold price has been collected for the same period. The information has been collected from the annual reports of NEPSE, Nepal Gem and Jewellery Association (NEGJA),Nepal gold market and Federation of Nepal Gold and Silver Dealer’s Association(FENEGOSIDA). The comparative analyses of gold market and capital market have shown the direct relationship between these two markets. The investors ‘tendency to switch to gold investment is found risky. The gold prices and interest rates have influence on NEPSE.